Pemenuhan Hak Ekonomi Pencipta Atas Karya Koreografi Dalam Kegiatan Komersil - Labobar, Navtaly Duestyn; Kuahaty, Sarah Selfina; Pariela, Marselo Valentino Geovani (KANJOLI Business Law Review, 2024)
In credit distribution carried out through digital banking services, approval of credit applications and data verification are The benefits derived from creating choreographic works include economic rights in the form of royalties. However, it is often the case that many copyright users use choreographers’ works for commercial performances without permission and without paying royalties. According to Article 9 of Law Number 28 of 2014 on Copyright, economic rights are the exclusive rights of the creator that arise from their own works. Therefore, the creator of choreographic works is entitled to receive economic rights in the form of royalties. If other parties use the copyrighted work without permission and do not pay the stipulated royalties, it constitutes an unlawful act. This study is a normative juridical research using statutory and conceptual approaches. The legal materials used are primary, secondary, and tertiary legal materials. The results of this study can be concluded that legal protection is necessary for copyright holders to ensure the fulfillment of their economic rights in the form of royalties and to provide legal protection for choreographic creators whose works are used by other parties in commercial activities, as well as the procedures to obtain economic rights in the form of royalties for the creators.